We are treated differently: Experiences of men who have sex with men in South African clinics - Tshivhase T. Ravele; Raikane J. Seretlo; Mathildah M. Mokgatle (South African Family Practice)
Background: Men who have sex with men (MSM) are regarded as a key population that needs specialised healthcare services to address their healthcare needs. This is because of their sexual practices. Men who have sex with men encounter positive and negative experiences when accessing healthcare services in public health care facilities. This study explored and described the experiences of MSM about accessing healthcare services in public healthcare facilities. The study was conducted in Ekurhuleni district, situated in the East of Gauteng province, South Africa.